Arthur Fleck’s Anxieties and Defense Mechanisms in Joker (2019) - Joel Zefanya Goha Paliaky; Theophilus Joko Riyanto (Institute of Research and Community Outreach - Petra Christian University, 2025)
This paper analyzes the anxieties and defense mechanisms experienced by the main character in Joker (2019), a psychological thriller that portrays the marginalization of individuals with mental illness. This film is interesting to analyze because it reflects real world issues, where people with mental illness are marginalized and mistreated by the society around them. The psychoanalysis theory of anxiety and defense mechanisms by Sigmund Freud is applied to analyse Arthur Fleck as the main character. He is a mentally unstable guy who works as a party clown. The findings show that Arthur’s anxieties are due to the mistreatments he received from people around him. Arthur went through reality, neurotic, and moral anxieties in his life, mainly because of the child abuse, rejection, the threats of cutting his paycheck, and the fear of breaking the social and moral standards. In response to these anxieties, Arthur ego applies defense mechanisms of repression, displacement, and rationalization. Repression is used to handle his neurotic anxiety. Displacement is used to manage his reality anxiety. Rationalization is used to cope with his reality and moral anxieties. In conclusion, although a person with a mental illness faces more hostile situations causing anxieties, he can handle them by himself.